2012
DOI: 10.1037/a0028035
|View full text |Cite
|
Sign up to set email alerts
|

Spiritually oriented treatment with Jewish clients: Meditative prayer and religious texts.

Abstract: The current paper examines the limited literature on spiritually oriented treatment with Jewish clients and suggests two novel techniques of integration. The paper reviews the differences that exist between various denominations of Jews and the unique issues that may surface in therapy with Jewish clients based on these denominational variations. The paper suggests some specific applications including integrating meditative prayer and sacred texts in psychotherapy with Jews. Additionally, the paper provides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…For example, Rosmarin, Pargament, Pirutinsky, and Mahoney () demonstrated via a randomized controlled clinical trial that spiritually integrated therapy based on traditional Jewish texts and ideas was effective at treating worry and stress. Similarly, Milevsky and Eisenberg () reported success with this form of intervention.…”
Section: Discussionmentioning
confidence: 86%
“…For example, Rosmarin, Pargament, Pirutinsky, and Mahoney () demonstrated via a randomized controlled clinical trial that spiritually integrated therapy based on traditional Jewish texts and ideas was effective at treating worry and stress. Similarly, Milevsky and Eisenberg () reported success with this form of intervention.…”
Section: Discussionmentioning
confidence: 86%
“…Since that time, researchers have noted the unique challenges members of the Jewish community may face in counseling, such as stereotypes; internalized anti‐Semitism; sexual orientation; intergenerational trauma; and issues related to Jewish identity, religious conversion, and observance of Jewish religious practices (Altman et al, ; Schlosser, ; Schnall, ). Furthermore, scholars have described several approaches to counseling Jewish clients, such as integrating Jewish spirituality (Frankel, ; Milevsky & Eisenberg, ; Weiss & Levy, ) into counseling; using storytelling and values (Schnall et al, ) in therapy; and with Orthodox clients, using culturally adapted cognitive behavior therapy (Huppert & Siev, ; Rosen et al, ).…”
Section: Counseling With the Jewish Populationmentioning
confidence: 99%
“…Religious Jews are more likely to attend religious services, celebrate Jewish holidays, believe in God, and identify with a religious denomination. Thus, several authors have described therapeutic interventions that incorporate Jewish spiritual practices into counseling (Milevsky & Eisenberg, ; Weiss & Levy, ). Furthermore, researchers have observed that spiritual practice is a protective factor against depression for Jews with high internal religiosity (Pirutinsky & Rosmarin, ).…”
Section: Complexities Of the Jewish Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, therapists must look for competencies they should possess to enable them to apply interventions effectively. For therapists, having sufficient background and information in religious and spiritual issues is a prerequisite to acquiring these tasks (Milevsky & Eisenberg, 2012;Saroglou, 2002). Meanwhile, therapy clients are willing to talk about religion and spirituality, which they consider as an appropriate part of the psychotherapy process.…”
mentioning
confidence: 99%